Establishment of Repertoire of Placentome-Associated MicroRNAs and Their Appearance in Blood Plasma Could Identify Early Establishment of Pregnancy in Buffalo (Bubalus bubalis) - Sarwalia, Parul; Raza, Mustafa; Soni, Apoorva; Dubey, Pratiksha; Chandel, Rajeev; Kumar, Rakesh; Kumaresan, A.; Onteru, Suneel Kumar; Pal, Ankit; Singh, Kalpana; Iquebal, Mir Asif; Jaiswal, Sarika; et al. (Frontiers in Cell and Developmental Biology, 2021)
Precise early pregnancy diagnosis in dairy animals is of utmost importance for an efficient dairy production system. Inability to detect dairy animal pregnancy sufficiently early after breeding results in extending unproductive time of their milk production cycle and causes substantial economic loss for dairy producers. Presently, most conventional and authentic pregnancy confirmation practice in cows and buffaloes is rectal palpation of reproductive organs at day 35-40 after insemination which sometime leads to considering an animal as false pregnant. Other alternative methods available for early pregnancy diagnosis lack either accuracy or reproducibility, or require elaborate instrumentation and laboratory set-up not feasible to practice at farmers door step. Present study aimed at establishment of the microRNA repertoire of the placentome, in buffaloes, which could capture event of the crosstalk between a growing embryo and a dam; through fetal cotyledons and maternal caruncles and thus could hint at early pregnancy establishment event in ruminants. Total RNA was isolated from buffalo placentome tissues during early stages of pregnancy (at day <25 and day 30-35), and global small RNA analysis was performed by using Illumina single end read chemistry and Bubalus bubalis genome. Total 2199 miRNAs comprising of 1620 conserved and 579 non-conserved miRNAs were identified. Stringent functional miRNA selection criteria could predict 20 microRNAs worth evaluating for their abundance in the plasma of pregnant, non-pregnant, cyclic non-bred and non-cyclic prepubertal animals. Eight of them (miR-195-5p, miR-708-3p, miR-379-5p, miR-XX1, miR-XX2, miR-130a-3p, miR-200a-3p, miR-27) displayed typical abundance patterns in plasma samples of animals on day 19 as well as 25 post insemination thus making them ambiguous candidates for early pregnancy detection. Similarly, higher abundance of the miR-200a-3p and miR130a-3p in non-pregnant animals were indicative of their utility for detecting animals as not pregnant. Importantly, miR-XX1 and miR-XX2 were characteristically abundant only in pregnant animals. In-silico target prediction analysis confirmed that these 2 miRNAs are important regulators of cyclooxygenase-2 (COX-2) and cell adhesion molecule-2 (CADM-2), both of which play significant role in implantation process during feto-maternal crosstalk. We interpret that circulatory miR-XX1 and miR-XX2 in blood plasma could be potential biomarkers for early pregnancy detection in buffaloes.